2018
DOI: 10.1037/adb0000327
|View full text |Cite
|
Sign up to set email alerts
|

Legalization of recreational marijuana and community sales policy in Oregon: Impact on adolescent willingness and intent to use, parent use, and adolescent use.

Abstract: Studies investigating the impact of medical marijuana legalization have found no significant changes in adolescent use. In one of the few studies focused on recreational marijuana, we investigated how recreational marijuana legalization and community sales policy influenced factors that likely impact youth use (youth willingness and intent to use, parent use) as well as youth use. Legalization of recreational marijuana in Oregon coincided with our study on adolescent substance use. Cohort 1 transitioned from 8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
50
2
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 70 publications
(58 citation statements)
references
References 36 publications
(45 reference statements)
4
50
2
1
Order By: Relevance
“…Some studies suggested that the prevalence of adolescence reporting cannabis consumption increased significantly in states that promoted decriminalization policy or legalized medical‐cannabis use . Yet, other authors have challenged this statement and they have suggested that the impact of cannabis legalization on youth consumption is unclear, in part because legalization has only recently been implemented in relatively few jurisdictions …”
Section: Common Clinical Adverse Effects Associated With Cannabinoidsmentioning
confidence: 99%
See 1 more Smart Citation
“…Some studies suggested that the prevalence of adolescence reporting cannabis consumption increased significantly in states that promoted decriminalization policy or legalized medical‐cannabis use . Yet, other authors have challenged this statement and they have suggested that the impact of cannabis legalization on youth consumption is unclear, in part because legalization has only recently been implemented in relatively few jurisdictions …”
Section: Common Clinical Adverse Effects Associated With Cannabinoidsmentioning
confidence: 99%
“…[4][5][6][7] Yet, other authors have challenged this statement and they have suggested that the impact of cannabis legalization on youth consumption is unclear, in part because legalization has only recently been implemented in relatively few jurisdictions. 3,8,9 Moreover, the public attitudes toward cannabis is more positive in these states, in which adults perceive cannabis as relatively "safe" compared with other psychoactive agents. 2,5,7 It is, therefore, important to evaluate the safety of cannabis according to the scientific rather than the popular literature.…”
mentioning
confidence: 99%
“…Non‐medical cannabis legalisation: Slight but significant increases in past 30‐day use among grade 8 and 10 students in Washington, but not among Colorado students or grade 12 Washington students . Some evidence of increases in frequency of use from a sample of Oregon users in grade 8–9 . Mixed evidence of legalisation effect among college students—increased use detected in a Washington college sample , but only among binge drinkers in an Oregon college sample .…”
Section: Resultsmentioning
confidence: 98%
“…Non‐medical cannabis legalisation: No significant post‐legalisation changes in initiation rates detected among early high school students in Oregon .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation